Effects of dietary supplementation with medicinal plant mixtures and immunostimulants on the immune response, antioxidant capacity, and hepatopancreatic health of Chinese mitten crab (Eriocheir sinensis) - Wang, Anran; Xu, Jie; Zhang, Xin; Liu, Xuran; Li, Mengge; Dong, Xiaojing; Miao, Shuyan (Frontiers in Immunology, 2024)
This study aimed to evaluate the efficiency of tea polyphenols (TP) and medicinal plant mixtures (Astragalus membranaceus + Lonicera japonica, Rheum officinale Bail + Scutellaria baicalensis + Platycladus orientalis) combined with astaxanthin (AST), benzoic acid (BA) and yeast complex on the health status of Eriocheir sinensis. A total of 630 crabs (male crabs: 41.51 ± 1.63 g; female crabs: 47.27 ± 0.79 g) were randomly distributed into seven groups with 3 replicates (male: female, 1:1). These crabs were fed as follows for 8 weeks: basal diet (M1), M2 (M1 + 100 mg/kg TP), M3 (M1 + 2.0 g/kg A. membranaceus + 20 g/kg L. japonica), M4 (M1 + 2.5 g/kg R. officinale Bail + 1.5 g/kg S. baicalensis + 1.0 g/kg P. orientalis), and M5, M6, M7 (M2, M3 and M4 added 600 mg/kg AST +1.0 g/kg BA + 20 mg/kg yeast complex, respectively). The results showed that the activities of acid phosphatase (ACP), alkaline phosphatase (AKP) and lysosome (LZM) in hemolymph were significantly increased in M5, M6 and M7 (P < 0.05), and the highest phagocytosis index (PI) and LZM activity were observed in M7 of female crabs. Moreover, the antioxidant indicators superoxide dismutase (SOD), glutathione (GSH), glutathione peroxidase (GPx) and catalase (CAT) of hepatopancreas were also significantly improved in M5, M6 and M7 (P < 0.05), while the malondialdehyde (MDA) contents showed an opposite trend. Furthermore, a morphological examination also showed the improved the histological structure of hepatopancreas in M7, especially as seen in the clear lumens, no vacuolation and integrity of basal membrane of hepatopancreatic tubule. Taken together, these results suggested that 2.5 g/kg R. officinale Bail, 1.5 g/kg S. baicalensis, and 1.0 g/kg P. orientalis in combination with 600 mg/kg AST, 1.0 g/kg BA, 20 mg/kg yeast complex could improve the non-specific immunity, antioxidant capacity, and hepatopancreatic health of E. sinensis.